Struktur Naratif Hikayat Nur Muhammad - Nur Fauzan Ahmad (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
This paper will review the narrative structure in Hikayat Nur Muhammad (HNM). The theory used is Aristotels and Abrams theory that is narrative structure of introductory unit, opening unit, middle unit and closing unit. The object of this study is the script of Nur Muhammad collection of the National Library of Jakarta with the number Bat. Gen. 378 C / Ml. 378 C. HNM is an old literary work of genre saga. HNM belongs to a kind of biographical narrative that has a narrative structure consisting of narrative units each of which has certain content categories, namely the opening unit, the middle and the cover. The introductory unit, the opening, the middle unit is the part that contains the core of the story. This unit is the most dominant and most important. The middle unit of the HNM contains the story of the patience and submission test that Nur Muhammad must undergo, the events of Nur Muhammad's creatures and dialogue with the four elements. The concluding unit is the conclusion of the image of the greatness of Nur Muhammad's character which further strengthens the image of the greatness of the Prophet Muhammad who was the beginning of this creation. Narrative Structure HNM supports the image of greatness, greatness and goodness of Nur Muhammad as a lover of God from whom created this universe.